The Spice Route and The Sub-Urban Muslim Community in South East Asia - Ali Mufrodi (Universitas Islam Negeri Sunan Kalijaga, 2022)
The spice route is the route that the spice trade passes from its home country, the Maluku Islands in particular, and the Archipelago Islands in general to other countries in the world. The spice route is thought to have existed for several centuries BC. The spice route stretches from the Maluku Islands/Nusantara to Malaya, India, Persia, Arabia, Egypt, to Europe. The Arabs took part in the spice trade from the Archipelago and the Persians, Indians, Malays, and the Chinese. When the Arabs embraced Islam and followed by the Persians and Indians, they passed and controlled the trade in the spice route. Since the first century to the twelfth century AD, Indian civilization with Hinduism and Buddhism dominated society and politics in Southeast Asia. Even the still Hindu solid kingdom in Java lasted until the end of the fifteenth century. During such a period, the Muslims became members of the marginalized communities on the spice route under the shadow of Hinduistic hegemony. However, they can play a role in the Islamization of the Southeast Asian Region through the spice route. Gradually the Muslims can shift the Hindu/Buddhist civilization and establish political power and build Islamic civilization. Islamic civilization includes, among others, the development of Islamic religious knowledge, shaping Islamic traditions in society, advancing education, and establishing political power. The writer used the 4-step historical method in this study, namely heuristics, criticism, interpretation, and historiography. He also applied acculturation theory to discuss this theme. Given the limited time, secondary sources were used to write this research.